Outgrowth Endothelial Cells (OECs): Cell-Based Therapy, Cell-Free Strategy, and Role of Senescence - Kadir, Rais Reskiawan A. (2022)
Background: Ischaemic stroke, emerging from an interference of blood supply leading to or within the brain, continues to be one of the main causes of mortality and disability worldwide. Since the disruption of the blood–brain barrier (BBB), primarily formed by brain microvascular endothelial cells (BMECs), and ensuing brain oedema have been associated with the enhanced risk of death in the early stages of ischaemic stroke, the discovery of novel agent(s) that can effectively repair endothelial integrity and overall BBB function is of paramount importance to mitigate stroke-related damages. In this regard, endothelial progenitor cells (EPCs), which are capable of replacing the dead or dying endothelial cells through directly differentiating into mature endothelial cells or indirectly via releasing various active compounds, may represent such agent. Methods: To assess the cerebral barrier-reparative effect of outgrowth endothelial cells (OECs), the functional subtype of EPCs, an in vitro model of human BBB was established by co-culture of human BMECs (HBMECs), astrocytes, and pericytes before exposure to oxygen-glucose deprivation alone or followed by reperfusion (OGD±R). Using a rodent model of middle cerebral artery occlusion (MCAO), this thesis subsequently assessed the therapeutic potential of OECs in vivo. Since the availability and functionality of EPCs may be adversely affected by age, the thesis then investigated the level of circulating EPCs and several elements known to regulate their mobilisation and survivability in elderly (n=40, 73.3±7.2 years) and young (n=50, 40.2±14.3 years) healthy individuals. An experimental model of chronological ageing, mimicked by repetitive culture of the cells up to passage 14, was employed to assess the effects of ageing on the morphology and functional properties of OECs. To elucidate the key mechanism underlies the limited functional capacity of aged OECs, so-called replicative senescence, the cells were treated either with specific inhibitor of NADPH oxidase, VAS2870 (5 M), or broad-spectrum anti-oxidant, vitamin C (0.5 M), starting at passage 12. To understand the pathological mechanisms involved in ischemic stroke and to provide a strong foundation for therapeutic target, a reverse translational research, which analysed the biochemical alteration of 90 ischaemic stroke patients compared to 81 healthy controls, was employed. The thesis eventually assessed the capacity of OEC-derived conditioned medium (OEC-CM), produced by exposure of OECs to hypoxic injury, to neutralise these changes using the aforementioned in vitro BBB model. Results Part I: Similar to HBMECs, OECs possessed classical endothelial characteristics, as observed by their typical cobblestone morphology and capacity to bind with FITC-UEA-1 and Dil-Ac-LDL. These cells also equipped with remarkable proliferative, migratory, and anti-oxidant capacity. They can integrate with resident brain endothelial cells and form a tight and functional BBB. Even so, exposing OECs to OGD±R impaired their function to a similar degree as HBMECs. Exogenous addition of OECs during OGD±R effectively repaired the integrity and function of an in vitro BBB model, as ascertained by the increases of transendothelial electrical resistance (TEER) and decreases of sodium fluorescein flux, respectively. Similar to these results, treatment with OECs also restored the scratch damage induced on the endothelial layer of the BBB model in serum-free conditions, and protected overall cerebral barrier integrity and function. These barrier-reparative effects have also been replicated in in vivo settings, with the intravenous administration of OECs 24 hours after induction to MCAO markedly decreasing the brain infarct volume in the ipsilateral hemisphere brain assessed on day 3 after treatment. The mechanistic studies showed that the suppression of oxidative stress and apoptosis of resident cerebral endothelial cells may mediate this barrier-reparative effect of OECs. Part II: An investigation to quantify the level of circulating EPCs in older versus younger healthy participants showed insignificant differences in the level of EPCs (CD34+CD133+KDR+) between these two groups. However, the number of cells exclusively expressing stemness markers and known to possess unique capacity to differentiate into mature endothelial cells (CD34+ and/or CD133+) sharply declines in the elderly. This phenomenon was followed by a decrease in total anti-oxidant capacity and simultaneous increases in plasma levels of inflammatory mediators, TNF-, and anti-angiogenic factors, endostatin and thrombospondin-1. The subsequent experimental studies to scrutinise the effect of ageing on molecular and functional phenotypes of OECs showed that chronological ageing profoundly perturbed the critical functions of these cells, and induced the appearance of multiple typical signs of replicative senescence. In line with the findings from clinical observational studies, senescent OECs also manifested decreased total anti-oxidant capacity along with the increased pro-oxidant NADPH oxidase activity and endostatin level. Suppressing oxidative stress level using anti-oxidants compounds, namely vitamin C or VAS2870, somewhat delayed OEC senescence and repaired their tubulogenic and BBB-forming capacities. Part III: A comprehensive analysis of plasma samples acquired from a large number of healthy volunteers and ischaemic stroke patients showed significant increases in the levels of TNF- during acute, subacute, and chronic phases of stroke. Further analysis from this study also showed that the level of this inflammatory mediator was significantly higher in healthy volunteers with endothelial dysfunction associated risk factors, such as hypertension, diabetes mellitus, and hyperlipidaemia than those without. The subsequent experimental studies also showed the dramatic impairment on the integrity and function of an in vitro BBB model exposed to high concentration of TNF-(10 ng/mL, 6 hours), as observed by the decreases in TEER value and concomitant increases in sodium fluorescein flux, respectively. Co-treatment with OEC-CM effectively negated the detrimental effects of TNF- on the BBB. The remarkable suppression on endostatin level, oxidative stress, apoptosis, stress fibre formation as well as the improvements in HBMEC and OEC viability, tubulogenic, and adhesion properties appeared to contribute to this protective effect. Conclusion: Treatment with OECs effectively repaired BBB damages in both in vitro and in vivo model of ischaemic stroke through suppressing oxidative stress and apoptosis of resident brain endothelial cells. While OECs provide the endogenous repair mechanism to counteract on-going brain endothelial injury, advanced age ultimately evokes senescence and cellular dysfunction. Nonetheless, regulating oxidative stress level appears to delay the appearance of senescence phenotype and protect overall stem cell function. An alternative cell-free strategy using OEC-CM effectively negated the detrimental effects of TNF-, an important inflammatory cytokine that was remarkably elevated in all phases of ischaemic stroke, on BBB integrity and function by simultaneously modulating a variety of mechanisms.